The inevitable colonisation of Singapore by Zika virus. Issue 1 (December 2016) - Fisher, Dale; Cutter, Jeffery
Abstract Singapore is endemic for Dengue virus, with approximately 10, 000 to 20, 000 annual cases reported in recent years. In 2012, Chikungunya was introduced, although the numbers of cases reported is much fewer. The current Zika virus pandemic originating in Brazil represents a threat to all regions with Aedes mosquitoes, particularly those well connected by travellers. In this respect, it was felt inevitable that Singapore would eventually realise its third endemic flavivirus. In late August 2016, a primary care practitioner observed a cluster of geographically linked patients attending with fever and rash. This resulted in the first identification of locally transmitted Zika in Singapore on August 27, 2016. This prompted a robust response in an attempt to stop further spread, which continued for approximately 10 days until a large number of laboratory-confirmed cases were found as a result of active case finding. Surprisingly, the strain was later identified to be of Asian lineage and distinct from that originating in the Americas, prompting speculation over the epidemiology of this under recognised virus in Asia.